'Netflix tax' from the perspective of national and EU audiovisual policies and what it brings to film funding in small states. (1st November 2021) - Kerševan Smokvina, Tanja
This article examines the approaches of two understudied small EU countries to the possibility of imposing film-related levies or production investment obligations on non-domestic video on-demand services. Though they can take various forms, such measures are commonly referred to as 'Netflix taxes'. Since 2018 they have been legally backed by the EU's Audiovisual Media Services Directive (AVMSD). By sharing evidence on how these measures have been taken up during the transposition of the AVMSD revisions in Croatia and Slovenia, the article contributes to the emerging body of research into cross-border financial contributions as a film funding tool. This evidence indicates that the potential of 'Netflix taxes' to solve the film funding problems in small national markets is limited. It is also argued that no significant contribution to the overall sustainability and diversity of European audiovisual production can be expected if these measures are implemented on a country-per-country basis.